Molecular characterization and pathogenicity study of serotype 8B fowl adenovirus isolated in Malaysia - Sabarudin, Nur Syazana (2019)
Inclusion body hepatitis (IBH) is an economic importance viral disease affecting broilers in many countries in this region including Malaysia. Depending on geographical locations, different serotypes of fowl adenovirus (FAdV) have been identified as the causative agent of IBH. The present study aimed to detect FAdV from suspected cases of IBH from commercial chicken farms in Malaysia based on amplification and sequencing of the hexon gene, to determine the phylogenetic tree of the identified FAdV isolates based on hexon gene sequence analysis, to determine the phylogenetic tree of serotype 8b FAdV isolate UPM/FAdV/420/2017 based on hexon and fiber gene sequence analysis and to determine the pathogenicity of serotype 8b FAdV isolate UPM/FAdV/420/2017 in specific-pathogen-free (SPF) chickens following inoculation of the virus via the oral route and intramuscular route. From the study, 16 cases of IBH from commercial chicken farms in Malaysia were detected positive for Fowl adenoviruses (FAdVs) by polymerase chain reaction (PCR). Result of phylogenetic analysis based on the hexon gene sequence confirmed the typing of all the 16 isolates into a single cluster of FAdV serotype 8b species E. One of the isolates, UPM/FAdV/420/2017 was opted for fiber gene sequencing and proceeded with phylogenetic analysis based on fiber gene sequence. The result of the fiber gene analysis supported the grouping of the isolate into FAdV species E. Subsequently, the pathogenicity of the isolate UPM/FAdV/420/2017 was characterized in 11-day old specific-pathogen-free (SPF) chickens following inoculation of the virus at 108.53 TCID50 via oral and intramuscular (IM) routes of inoculation. Infected chickens showed clinical signs of depression, ruffled feathers, huddling, inappetence, diarrhea and gross lesions characteristic of IBH such as enlarged, pale-yellowish liver with necrotic foci. Chickens infected via the IM route showed significantly higher clinical score values (p<0.05) and higher percent mortality than orally inoculated birds. Histopathologic examination of the liver in infected chickens showed the presence of intranuclear inclusion bodies with a higher degree of severity in IM infected groups (p<0.05). The amount and duration of virus shedding differ significantly between the two infected groups (p<0.05) with IM-inoculated chickens secreted higher amount of virus and the shedding last until the last sampling point at 28 dpi. Meanwhile, the amount of virus shedding of the oral group was lower and was detected until the 14-day pi. At day 5 postinoculation, virus copy number (VCN) (> log10 9) was recorded highest in the liver and gizzard irrespective of inoculation. Although other organs namely cecal tonsils, bursa, kidney, spleen, and thymus were detected positive for FAdV, no significant gross and microscopic lesions were detected in these organs except the liver. The antibody response against FAdV showed a statistically significant difference (p<0.05) between oral and IM-inoculated groups. Higher values were recorded in IM-inoculated chickens throughout the experimental trial. Results of the study suggested that FAdV serotype-8b is a dominant serotype circulating in Malaysia and associated with outbreaks of IBH. This study also confirmed that Malaysian FAdV-8b isolate UPM/FAdV/420/2017 is a pathogenic virus and caused symptomatic IBH in SPF birds. The study approved that the extent of pathogenicity can be influenced by the route of inoculation. Further study is underway on the ability of inactivated FAdV vaccine in conferring protection against this virus.